146k views
3 votes
Enter a number in the box to make this a true number sentence.
5*(6 - 4) = (5x6) -(5x__)

Enter a number in the box to make this a true number sentence. 5*(6 - 4) = (5x6) -(5x-example-1
User Geoffc
by
4.7k points

2 Answers

5 votes

Answer:

4

Explanation:

because if you look at first 5x(6-4) split them and you get (5x6) and (5x4)

hope you like answer

User Yellow Days
by
5.7k points
7 votes

Answer:

4

Explanation:

5 x 6-4 = 20

5x6 - 5x4 = 20

User CermakM
by
6.1k points